Outsourcing as a Challenge for Achieving Competitive Advantage in Road Freight Industry – The Case of Croatia - Naletina, Dora; Petljak, Kristina; Rožić, Tomislav (Promet - Traffic&Transportation, 2020)
The purpose of this study was to explore outsourcing as a possible source of competitive advantage for road freight operators, with the empirical research directed towards the road freight transportation sector. Methodologically, this study drew on the data collected from a sample of Croatian road freight transporters. Because a certain number of transportation companies tend to outsource their resources, the insight into outsourcing activities was gained through analysing (1) the number of hired vehicles in the fleet (outsourced vehicles), and (2) the number of hired drivers (outsourced drivers). A variance inflation test, correlation and multiple regression analysis were conducted to test the model assumptions. The research results confirmed the connection between the externalised resources and the differentiation of services and staff. The main contribution and managerial implications included that the companies with a more significant number of hired vehicles in their fleet should differentiate their services. In contrast, the companies that own the majority of their vehicles should build their competitive advantage through staff differentiation.